Culture wars in American education : past and present struggles over the symbolic order - Olneck, Michael R. (New York : Routledge, 2024)
"Culture Wars in American Education: Past and Present Struggles over the Symbolic Order radically questions norms and values held within US Education, and analyses why and how culture wars in American education are intense, consequential, and recurrent. Applying the concept of "symbolic order," this volume elaborates ways in which symbolic representations are used to draw boundaries, allocate status, and legitimate the exercise of authority and power within American schooling. In particular, the book illustrates the "terms of inclusion" by which full membership in the national community is defined, limited, and contested. It suggests that repetitive patterns in the symbolic order, for example, the persistence of the representation of an individualistic basis of American society and polity, constrain the reach of progressive change. The book examines the World War I era Americanization movement, the World War II era Intercultural Education movement, the late-20th century Multicultural Education movement, continuing right-wing assaults on Ethnic Studies and Critical Race Theory in the first decades of the 21st-century, and historical and contemporary conflicts over the incorporation of languages other than Standard English into approved instructional approaches. In the context of continuing culture wars in the United States and across the globe, this book will be of interest to graduate students and scholars in critical studies of education, history of education, sociology of education, curriculum theory, multicultural education, and comparative education, as well as to educators enmeshed in contemporary tensions and conflicts"--
Americanization and the Education of Immigrants, 1900-1925: An Analysis of Symbolic Action -- The Recurring Dream: Symbolism and Ideology in Intercultural Education and Mainstream Multicultural Education -- Many More Tucsons? Ethnic Studies in Public Schools -- Regulating Language: Why Did Oakland's Ebonics Resolution Cause a Language Panic and California's Proposition 227 Did Not? -- Retreat from Nativism? Dual Language Education -- What Have Immigrants Wanted from American Schools? What Do They Want Now? Historical and Contemporary Perspectives on Immigrants, Language, and American Schooling.
Keywords: Immigrants -- Education -- United States -- History; Culture conflict -- United States; Americanization -- History -- 20th century; Multicultural education -- United States; Ethnology -- Study and teaching -- United States; Education, Bilingual -- United States; EDUCATION / Educational Policy & Reform / General; EDUCATION / Philosophy & Social Aspects; EDUCATION / Organizations & Institutions